Wykorzystanie elementów terapii akceptacji i zaangażowania we wsparciu seniorów = Using elements of acceptance and commitment therapy in supporting seniors - Arendt, Ilona (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In recent years, European countries have been observing a progressive process of population ageing. This is primarily due to the decline in fertility rates, a higher percentage of external migration of people of working age compared to internal migration, and increasing life expectancy. These undeniable demographic shifts bring about changes in the social, cultural, political and economic spheres. For each of these spheres, the issue of seniors is increasingly becoming a topic requiring attention and the introduction of various solutions on both micro and macro scales.
Keywords: senior; terapia; wsparcie; terapia akceptacji i zaangażowania (ACT); stowarzyszenia; dom pomocy społecznej; starzejące się społeczeństwo; seniors; therapy; support; Acceptance and Commitment Therapy (ACT); associations; social welfare home; ageing society